2021
DOI: 10.1088/1755-1315/910/1/012131
|View full text |Cite
|
Sign up to set email alerts
|

The Estimation of Iron, Zinc, Phytic Acid Contents and Their Molar Ratios in Different Types of Bread and Rice Consumed in Halabja City, Iraqi Kurdistan

Abstract: A total of 10 samples involving five bread and five rice types and five cooked rice were selected. The iron and Zn contents were analyzed using an Inductively Coupled Plasma Mass Spectrophotometer (ICP-MS), and phytic acid content was analyzed using a rapid colorimetric method using a spectrophotometer. Phytic acid to Fe and Zn molar ratios were also determined using their molar weight to determine the potential bioavailability of selected nutrients. A one-way ANOVA test was used to statistically analyze the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…In compare, the range of Zn concentration ranged from 97.34 to 121.76 mg kg -1 in the rice samples from the main industrial areas of Bangladesh (Hasan et al, 2022). In accordance with our results, the concentrations of Zn in the rice samples ranged from 8.66 to 17.4 in two type of rice (Salih et al, 2021). This might due to the high capacity of Zn absorption, which causes a decrease in the availability of Zn in calcareous soils in Iraqi Kurdistan (Mam-Rasul, 2019).…”
Section: Chromiumsupporting
confidence: 89%
See 1 more Smart Citation
“…In compare, the range of Zn concentration ranged from 97.34 to 121.76 mg kg -1 in the rice samples from the main industrial areas of Bangladesh (Hasan et al, 2022). In accordance with our results, the concentrations of Zn in the rice samples ranged from 8.66 to 17.4 in two type of rice (Salih et al, 2021). This might due to the high capacity of Zn absorption, which causes a decrease in the availability of Zn in calcareous soils in Iraqi Kurdistan (Mam-Rasul, 2019).…”
Section: Chromiumsupporting
confidence: 89%
“…Similarly, the concentrations of Fe in the rice samples ranged from 10.8 to 45.3 mg kg -1 in two type of rice studied by (Salih et al, 2021). This might be due to presence low content of Fe in rice grain grown in Kurdistan region which the soils are calcareous and contain low amount of available Fe (Rasheed and Salih, 2020).…”
Section: Chromiummentioning
confidence: 95%
“…The findings of Hama- Salih et al (2021) showed that the rice samples in their study had poor bioavailability of Fe and Zn because of high PA:Fe and PA:Zn molar ratios. It can be due to the high PA content in the studied rice, which impacted Fe and Zn content bioavailability in these foods.…”
Section: Discussionmentioning
confidence: 89%